2020
DOI: 10.32598/ijpcp.26.3405.1
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Stress Level of Health Care and Non-health Care in Exposed to COVID-19 Pandemic

Abstract: Objectives: The sudden outbreak of Coronavirus (COVID-19) as a deadly disease worldwide has caused widespread psychological problems and physical problems. Given the importance of preventing and controlling mental health problems in patients with this disease, the present study was conducted to investigate the Perceived Stress level of health care and non- health care in Exposed to COVID-19 pandemic. Methods: This is a descriptive-cross-sectional study conducted in April 2020. A total of 528 medical and non-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…In Sirati Nir et al's study (2020), the level of stress in clinical HCWs exposed to COVID-19 was also higher than in nonclinical practitioners. Furthermore, 90.2% of the individuals reported moderate levels of stress (37). In the present study, in terms of anxiety and insomnia, 86.1% and 4.3% of the EMS practitioners were at good and mild levels, respectively.…”
Section: Discussionsupporting
confidence: 44%
“…In Sirati Nir et al's study (2020), the level of stress in clinical HCWs exposed to COVID-19 was also higher than in nonclinical practitioners. Furthermore, 90.2% of the individuals reported moderate levels of stress (37). In the present study, in terms of anxiety and insomnia, 86.1% and 4.3% of the EMS practitioners were at good and mild levels, respectively.…”
Section: Discussionsupporting
confidence: 44%
“…If these problems are not taken into account, they may create irreparable consequences for these people [31,32]. On the other hand, more than a year after the outbreak of COVID-19, we are still witnessing the mutation of this deadly virus on a global scale, and a definite date for the post-corona era is inconceivable [33,34]. Thus, it is necessary to seek solutions to improve the mental health of hospital nurses and doctors.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently little research on this topic with smaller sample size; thus, we could not compare the results of our study extensively with previous studies. Authors (22) have compared 528 participants of HCWs with non-HCWs and reported that nursing students were more stressed than formal and contractual nurses. Also, therapeutic HCWs were more stressed than nontherapeutic workers.…”
Section: Discussionmentioning
confidence: 99%